Molecular cloning, genomic analysis, and biological properties of rat leukemia virus and the onc sequences of Rasheed rat sarcoma virus. - Gonda, M A (1982)
Rasheed rat sarcoma virus (RaSV) has been shown to code for a protein of 29,000 Mr not present in replication-competent rat type C helper virus (RaLV)-infected cells. This protein is a fused gene product consisting of a portion of the RaLV p15 gag protein and the transformation-specific 21,000 Mr (p21) ras protein, which is also found in Harvey murine sarcoma virus. We now report the molecular cloning of both the SD-1 (Sprague-Dawley) strain of RaLV and the transforming ras sequences of RaSV. Heteroduplex analysis of these cloned DNAs demonstrated that the RaSV ras gene (v-Ra-ras) was inserted into the rat type C viral genome with a small deletion of RaLV genetic information in the 5' region of the gag gene and that the v-Ra-ras gene (0.72 kilobase pair) is homologous to and colinear with the p21 ras gene of Harvey murine sarcoma virus (v-Ha-ras). Restriction enzyme mapping confirmed the homology demonstrated by heteroduplex mapping, showing strong site conservation of restriction endonucleases known to cleave v-Ha-ras. Cloned v-Ra-ras DNA transformed NIH 3T3 cells, inducing the synthesis of the p29 RaSVgag-ras protein.